2005
DOI: 10.1128/mcb.25.4.1569-1575.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of SOCS-3 by Resistin

Abstract: Resistin is an adipocyte hormone that modulates glucose homeostasis. Here we show that in 3T3-L1 adipocytes, resistin attenuates multiple effects of insulin, including insulin receptor (IR) phosphorylation, IR substrate 1 (IRS-1) phosphorylation, phosphatidylinositol-3-kinase (PI3K) activation, phosphatidylinositol triphosphate production, and activation of protein kinase B/Akt. Remarkably, resistin treatment markedly induces the gene expression of suppressor of cytokine signaling 3 (SOCS-3), a known inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
182
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(202 citation statements)
references
References 43 publications
11
182
0
9
Order By: Relevance
“…However, it attenuates the insulin-signaling pathway upon decreased insulindependent phosphorylation of the insulin receptor and subsequent reduction of downstream 9 signals [56]. Suppressor of cytokine signaling (SOCS) proteins are well known inhibitors of insulin signaling.…”
Section: Resistin Obesity and Markers Of Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…However, it attenuates the insulin-signaling pathway upon decreased insulindependent phosphorylation of the insulin receptor and subsequent reduction of downstream 9 signals [56]. Suppressor of cytokine signaling (SOCS) proteins are well known inhibitors of insulin signaling.…”
Section: Resistin Obesity and Markers Of Insulin Resistancementioning
confidence: 99%
“…In adipocytes, resistin activates SOCS3 in a time-and dose-dependent manner and induces the association of SOCS3 with the insulin receptor. It is possible that SOCS3 could be a cellular mediator of the ability of resistin to antagonize insulin action in adipocytes [56].…”
Section: Resistin Obesity and Markers Of Insulin Resistancementioning
confidence: 99%
“…From this perspective, the ability of RETN to affect glucose metabolism is associated with activation of SOCS-3, an inhibitor of insulin signaling in adipocytes (Steppan et al, 2005). Although studies in animal models have consistently shown that RETN promotes insulin resistance, there is also evidence indicating that this effect in humans is less evident (Lee et al, 2003;Heilbronn et al, 2004).…”
Section: Resistinmentioning
confidence: 99%
“…Several reports have demonstrated that ectopic expression of SOCS3 may lead to insulin resistance (Senn et al 2003;Steppan et al 2005;Ye et al 2012;Jorgensen et al 2013). As shown in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Resistin antagonize several insulin actions in vitro, resulting in decreased basal and insulin-stimulated glucose uptake, oxidation and glycogen synthesis. For example, recombinant resistin attenuates insulin-stimulated glucose uptake by inducing the expression of SOCS3 in 3T3-L1 adipocytes (Steppan et al 2001;Steppan et al 2005). Basal and insulin-stimulated glucose uptake, oxidation and glycogen synthesis in L6 rat skeletal muscle cells were also decreased in the presence of resistin (Palanivel et al 2006).…”
Section: Introductionmentioning
confidence: 98%